The Impact of Technical Competency, Experience and Communication Skills on the Level of ICT Innovation in Tanzania - Lubuaa, Edison Wazoel (University of Dar es Salaam Library Journal, 2022)
This study determined the impact of the technical competency, communication skills, and the experience of experts on the level of ICT innovation in an organisation. The study is relevant to Tanzania because the country depends on imported technological business solutions, which could be developed in the country. The study used the survey strategy, with 116 respondents representing different organisations within Tanzania. The study used the structured questionnaire as a tool for data collection. Additionally, the study conducted an analysis using inferential statistics to test hypotheses. The findings of the study concluded that the technical competency of experts, the level of communication skills and the experience of experts in dealing with complex projects significantly impacted the level of ICT innovations within Tanzania. This study recommends the improvement of the experts ' technical skills, ability to deal with complex projects, and ability to communicate their innovation needs. This improvement will contribute to the increase of innovative products among local organisations.